PERAN BRIEF COGNITIVE BEHAVIOR THERAPY UNTUK PENINGKATAN HARGA DIRI PADA PEREMPUAN LAJANG - Sabatini Anggawijaya; Hartanti Hartanti (CALYPTRA, 2018)
Single status for women is sometimes regarded as a worrying phenomenon especially for women. This single status can lead to negative stigma of society especially for women aged 35 years and over. This negative stigma often raises negative judgments for single women. Negative judgments in women can lead to the emergence of irrational thoughts or so-called cognitive distortions. In addition, the existence of less adaptive behaviors such as lack of social ability also contribute in shaping one's self esteem. This distortion and less adaptive behavior can create low self-esteem for women and make them less likely to feel less valuable when dealing with the social environment. The purpose of this study is to examine the role of brief cognitive behavior therapy (CBT) to increase self-esteem in single women. There were two participants in the study. Both are single women aged 35-45 years, still want to get married, and have low self esteem. This research was conducted with one group pretest-posttest design. Assessment techniques used consisted of observation, interviews, cognitive distortion questionnaires, self-esteem questionnaires, and personality assessments of BAUM, DAP, HTP, DCT, and TAT. The results showed a significant value of 0.180 (sig> 0.05). In addition, there is an increase in value and self-esteem category and effect size test results of 0.9489 (z> 0.5). This suggests that the effect of CBT briefing on self-esteem increases. The change in cognitive distortion of the two participants was more positive than before the CBT brief was given. Changes in both participants were limited to cognitive levels only and no behavioral changes had occurred. This is because both participants are now more focused on their work.